Late-Holocene paleoenvironmental and land-use changes in Western Greece based on a sediment record from Klisova lagoon - Emmanouilidis, Alexandros; Panagiotopoulos, Konstantinos; Kouli, Katerina; Avramidis, Pavlos (The HoloceneThe Holocene, 2022)
In this study, we present the findings of a sediment core retrieved from Klisova lagoon, Western Greece, an area with a long record of documented human presence. The recovered deposits were subjected to sedimentological, XRF, and micropaleontological analyses. For the last 4700 cal BP, the freshwater influx, the progradation of the Evinos river delta and related geomorphological changes control the environmental conditions in the lagoon. Considering the centennial temporal resolution of our analyses, small offsets of c.a. 50?years due to lack of regional reservoir correction do not considerably impact the reported radiocarbon ages. Prior to 4000 cal BP, a relatively shallow water depth, significant terrestrial/freshwater input and increased weathering in the lagoon area are inferred. Elemental proxies and increased dinoflagellate cyst and foraminiferal abundances, which indicate marine conditions with prominent freshwater influxes, point to the gradual deepening of the lagoon up to 2000 cal BP. The marine and freshwater condition equilibrium sets at 1300 cal BP, with the lagoonal system reaching its present state. Maxima of anthropogenic pollen indicators during the Mycenaean (3200 cal BP), Hellenistic (2200 cal BP), and Late Byzantine (800 cal BP) periods suggest intervals of increased anthropogenic activities in the area.